Architectural thought : the design process and the expectant eye - Brawne, Michael, 1925-2003; ebrary, Inc. (Amsterdam : Architectural Press, 2003)
An introduction to architectural thought, this text is a thorough and accessible discussion in search of the principles of the design process. Documenting the non-verbal processes and decisions that architects and designers make is a difficult task, but one that is important when trying to understand the development of architectural design through the ages. Michael Brawne uses his experience as a practicing architect, academic and educator to provide an overview of the subject. By looking at the practices and buildings of architects past and present he incorporates history and philosophy in the search for a theory of design.
Time -- Two temples -- Can we describe how we design? -- Three monuments -- Witnesses -- Thinking & drawing -- Was it like this? -- Travel, books & memory -- The vernacular & style -- Materials -- Structure -- Light -- Architecture & language -- Looking at pictures -- The office & the school -- Does it matter? -- Critical innovation
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: architektonický design; architektura -- filozofické aspekty; architectural design; architecture -- philosophical aspects; monografie; e-knihy online; monographs; e-books online